THE MAXIM VIOLATION OF RAJA PARHATA IN MARTONGGO RAJA BATAK TOBA CEREMONY - Indah Suryani Ompusunggu; I Wayan Dirgeyasa Tangkas (Universitas Negeri Medan, 2020)
This study discussed about the maxim violation of Raja Parhata in Martonggo Raja Batak Toba ceremony. The aims of this study were to analyze the kinds of maxim of violation of Raja Parhata and reasons of maxim of violation occurred in Martonggo Raja Batak Toba Ceremony. This study conducted by using descriptive qualitative method. The data of this research was from the utterances of Raja Parhata. The source data were from two Martonggo Raja videos and two informants of Raja Parhata. The writer found violation of maxim of quantity with total number 28 utterances (46.6%), violation of maxim of quality with total number 3 utterances (5%), violation of maxim of relation with total number 21 utterances (35%) and violation of maxim of manner with total number 8 utterances (13.4%). There were four reasons of the Raja Parhata did violation of maxims in Martonggo Raja Batak Toba ceremony, namely to show respect (43 utterances, 71,6%) is the most reason. Besides, the Raja Parhata also change the topic (15 utterances, 25%), and the fewest reason is to keep a secret (2 utterances, 3,4%).